Floating Window pada Sistem Lelang Online yang Terhubung dengan Akun Instagram menggunakan Firebase Realtime Database Berbasis Android - Winlian Winlian; Rolly Intan; Lily Puspa Dewi (Jurnal Infra, 2021)
Buy and sell is one of the activity that is so general in eachcountry. There are many various ways to do it. Online ouction isone of it and it help the auction opener easier to find the highestprice offer from auction bidder even they are from the distanceplaces. In Indonesia, many online auction have been done and oneof it using Instagram as their platform. But, online auction fromInstagram has so many deficiency that causes the uncomfortablefor the online auctioneer.So this application was made and it connects with Instagram,where the user can make an auction on the application and focuswith the notification from the running application. The user canalso trust the potential bidder with the social capital which isincluded in the user’s Instagram account. This application has apin feature that using floating window for choosen bidder inapplication and the process is display in realtime.According to the result of test from 20 respondents as a potentialbidder and 5 person as an auction maker, the application can helpthe process of online auction with average 89% from the potentialbidder side and 84% from auction maker side. Notification iseffective and communicative with average 83% from the bidderside and 76% from the auction maker side. Floating window helpswith average 84% from the potential bidder side and 76% fromauction maker side. So, the conclusion is this application can helpand give a place for the online auctioneer in Instagram.